2012
DOI: 10.1111/j.1600-0854.2012.01376.x
|View full text |Cite
|
Sign up to set email alerts
|

Snail Destabilizes Cell Surface Crumbs3a

Abstract: During Epithelial to Mesenchymal Transition (EMT), cells modulate expression of proteins resulting in loss of apical-basal polarity. Effectors of this EMT switch target the polarity protein Crumbs3a, a small transmembrane protein that is essential for generation of the apical membrane and tight junctions of mammalian epithelial cells. We previously showed that the Crumbs3 gene is a direct target of transcriptional regulation by Snail, a potent inducer of EMT. However, Snail has also been shown to have multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 72 publications
(93 reference statements)
0
22
0
2
Order By: Relevance
“…Like the native Crumbs3a protein, SNAP-Crumbs3a is distributed over the entire apical surface and is more highly concentrated at or near the tight junctions (Harder et al, 2012; Fig. S2 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the native Crumbs3a protein, SNAP-Crumbs3a is distributed over the entire apical surface and is more highly concentrated at or near the tight junctions (Harder et al, 2012; Fig. S2 A).…”
Section: Resultsmentioning
confidence: 99%
“…To examine surface delivery of another apical protein, we used a previously characterized MDCK cell line expressing SNAP-tagged Crumbs3a (Harder et al, 2012). Like the native Crumbs3a protein, SNAP-Crumbs3a is distributed over the entire apical surface and is more highly concentrated at or near the tight junctions (Harder et al, 2012; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To show that MCF-7 cells have these features, we evaluated the effects of E2 on the expression of CRB3, a novel epithelial marker [15], and N-cadherin, a mesenchymal marker. CRB3 is the human ortholog of the crumbs (CRB) protein and is required to establish the apical membrane, define the basolateral plasma domain, and has a fundamental function in the establishment of morphogenesis of 3D epithelial cell cultures [43].…”
Section: Discussionmentioning
confidence: 99%
“…CRB3 is the human ortholog of the crumbs (CRB) protein and is required to establish the apical membrane, define the basolateral plasma domain, and has a fundamental function in the establishment of morphogenesis of 3D epithelial cell cultures [43]. CRB3 is a tumor suppressor during the transformation and progression of mammalian epithelial cells; its loss favors tumor cell growth, metastasis, and EMT [15,44]. We found that E2 downregulates CRB3 expression in MCF-7 cells; therefore, it is possible that CRB3 could be used as a novel marker in EMT, and its role in breast carcinogenesis has just begun to be unveiled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation